Attenuation of brain mitochondria oxidative damage by Albizia julibrissin Durazz: neuroprotective and antiemetic effects. (4th March 2019) - Ebrahimzadeh, Mohammad Ali; Fathi, Hamed; Ziar, Ali; Mohammadi, Hamidreza
Abstract: Medicinal plants, as new drugs, are considered for treatment of insomnia, anxiety, depression, confusion, nausea, and vomiting symptoms. The current study aimed to evaluate the neuroprotective and antiemetic effects of Albizia. julibrissin Durazz. flower extract in the chickens. Emesis was induced by copper sulfate and ipecac (60 and 600 mg/kg, orally, respectively) and the methanolic extract (50, 100, and 200 mg/kg) were injected intraperitoneally (i.p.). Mitochondrial function, lipid peroxidation (LPO), protein carbonyl (PC) content, and catalase activity as biomarkers of oxidative damage were evaluated in the brain mitochondria. All doses of extract showed significant ( p  < 0.001) antiemetic activity against induced emesis by copper sulfate and ipecac. Brain mitochondria function (by 50, 100, and 200 mg/kg of extract) were increased 48%, 85%, and 90% against emesis induced by ipecac and 32%, 18%, and 24% against emesis induced by copper sulfate, respectively. LPO and PC contents were significantly decreased after the administration of extract in emesis induced by copper sulfate and ipecac. A significant decrease ( p  < 0.01) of CAT activity was observed in the extract (200 mg/kg) group in emesis induced by copper sulfate in chickens brain mitochondria. The present study suggests that the extract had antiemetic effects against emesis induced by copper sulfate and ipecac in young chickens via peripheral and central mechanisms. Neuroprotective effect of the extract could be due to the increase in bioactive compounds, plasma antioxidants, or direct free radical scavenging that could prevent lipid and protein alteration and impede the formation of oxidative damage.